1992
DOI: 10.1073/pnas.89.22.11036
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-repair coupling determines the strandedness of ultraviolet mutagenesis in Escherichia coli.

Abstract: We have analyzed the spectra of UV-induced mutations in the Lad gene of a wild-type and an mfd strain of Escherichia coli. mfd strains have been recently proposed to be deficient in a factor coupling DNA repair and transcription. Analysis of UV-induced mutations occurring at adjacent pyrimidines showed that mutations in the wild-type strain arose largely from the nontranscribed strand but arose predominantly from the transcribed strand in the mfd strain. The overall strand switch was 14-fold. One mutation, G-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 45 publications
2
40
1
Order By: Relevance
“…4). These results are consistent with studies that have demonstrated a moderate increase in UV sensitivity of cells defective in transcription-coupled repair such as mfd mutants of E. coli (23) (Fig. 4) and CS cells (24,25).…”
Section: Methodssupporting
confidence: 82%
“…4). These results are consistent with studies that have demonstrated a moderate increase in UV sensitivity of cells defective in transcription-coupled repair such as mfd mutants of E. coli (23) (Fig. 4) and CS cells (24,25).…”
Section: Methodssupporting
confidence: 82%
“…In a disruption mutant of RAD26, a marked reduction in TRC was observed in the RPB2 gene compared with that in wild-type (wt) cells while the removal of CPDs from the genome overall was unaffected (41). In addition, no marked increase in UV sensitivity was observed for the rad26 cells compared with wt cells (41), similar to what is observed with mfd mutant cells (9,28). Thus, it appears that RAD26 encodes a TRC factor in S. cerevisiae (41).…”
supporting
confidence: 63%
“…Outside of this promoter region, however, in which slower repair was found, several mutagenesis hot spots were detected as in the pyrimidine clusters CTTT and CCCTCT at positions 54 and 89, respectively (Armstrong and Kunz 1990). Another example of higher mutagenesis in the TS was observed previously in mfd-deficient E. coli lacking the TCR process (Oller et al 1992). These results are in contrast with those of the TSs of RNAP II genes that are preferentially repaired and, consequently, show a lower mutagenesis as compared with the NTSs (Vrieling et al 1989;McGregor et al 1991;Sage et al 1993).…”
Section: Mutagenesis Is Linked To Nucleotide Excision Repaircontrasting
confidence: 54%